ON INCLUSION BETWEEN \(ΛBV^(p)\), CHANTURYIA AND \(H_ω^p\) CLASSES - Ledari, Alireza Ahmadi; Naderi, Habib (Italian Journal of Pure and Applied Mathematics, 2015)
Dedicated to the memory of professor Parviz Azimi In this paper we prove inclusion relations between \(ΛBV^(p)\) and V[v] and give a necessary condition for the inclusion of (ΛBV^(p)\) in classes \(H_ω^p\).